2000
DOI: 10.1542/peds.106.1.115
|View full text |Cite
|
Sign up to set email alerts
|

New Immunoassay in Stool Provides an Accurate Noninvasive Diagnostic Method forHelicobacter pyloriScreening in Children

Abstract: The new, noninvasive, low-cost H pylori antigen test in stool can replace the UBT for detection of H pylori infection in children with comparable reliability and accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 21 publications
3
54
0
Order By: Relevance
“…13 C]urea breath test ( 13 C-UBT) and a new developed immunoassay for the detection of Helicobacter pylori antigens in stool, the H. pylori stool antigen test (HpSA) (3), are noninvasive tests for H. pylori diagnosis.…”
Section: The [mentioning
confidence: 99%
“…13 C]urea breath test ( 13 C-UBT) and a new developed immunoassay for the detection of Helicobacter pylori antigens in stool, the H. pylori stool antigen test (HpSA) (3), are noninvasive tests for H. pylori diagnosis.…”
Section: The [mentioning
confidence: 99%
“…Many studies support the diagnostic value of H. pylori antigens in stool samples by enzyme immunoassay (EIA) (8).This test was approved in 1998 for both diagnosis and monitoring the response to treatment of H. pylori infection in adult patients (9). Recently, a study performed by Falsafi T et al using stool test for detection of H. pylori antigen in children and adolescents from Tehran demonstrated a high prevalence of infection (70%) in cases with a family history of H. pylori infection or peptic ulcer disease (10).…”
Section: Introductionmentioning
confidence: 99%
“…In another serology based Turkish study held in asymptomatic subjects, 30% of the teenagers and 70% of the adults already acquire H. pylori infection (Us and Hascelik 1998). In previous studies, the sensitivity and specificity of the HpSA test were found to be comparable to the UBT (Casswall et al 1999;McNamara et al 1999;Braden et al 2000), but there are only a few studies investigating the correlation between HpSA OD values and gastric inflammation scores or H. pylori load. The reaction velocity of the biopsy urease test, the ∆ 13 C value of the UBT and the OD value of the HpSA test correlated well with H. pylori density in the stomach (Labenz et al 1996;Chou et al 1997;Chang et al 2002).…”
Section: Discussionmentioning
confidence: 96%